Factors affecting N‐terminal pro‐brain natriuretic peptide elevation in the acute phase of Kawasaki disease. Issue 11 (14th July 2016) - Yanagisawa, Daisuke; Ayusawa, Mamoru; Kato, Masataka; Watanabe, Hirofumi; Komori, Akiko; Abe, Yuriko; Nakamura, Takahiro; Kamiyama, Hiroshi; Takahashi, Shori
Abstract: Background: The aim of this study was to investigate the clinical significance and factors that affect N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) elevation in the acute phase of Kawasaki disease (KD) despite the absence of apparent cardiac complications. Methods: The laboratory and echocardiography results of 44 KD patients in the acute and subacute phases were reviewed. Results: With preserved cardiac function, median NT‐proBNP was significantly elevated in the acute phase compared with the subacute phase (343 pg/mL, IQR, 162–1182 pg/mL vs 98 pg/mL, IQR, 61–205 pg/mL, respectively; P < 0.0001). The respective levels of tumor necrosis factor (TNF)‐α, soluble TNF receptor (sTNFR)1, and sTNFR2 were also significantly elevated in the acute phase compared with the subacute phase: TNF‐α, 3.3 pg/mL (IQR, 2.6–4.8 pg/mL) versus 2.4 pg/mL (IQR 1.9–4.0 pg/mL; P < 0.01), sTNFR1, 2741 pg/mL (IQR, 2080–3183 pg/mL) versus 976 pg/mL (IQR, 814–1247 pg/mL; P < 0.0001), sTNFR2, 5644 pg/mL (IQR, 4693–7520 pg/mL) versus 3169 pg/mL (IQR, 2132–3878 pg/mL; P < 0.0001). Log‐transformed NT‐proBNP was correlated with TNF‐α (r = 0.29, P = 0.056), sTNFR1 (r = 0.60, P < 0.0001), and sTNFR2 (r = 0.65, P < 0.0001). TNF‐α was correlated with sTNFR1 (r = 0.35, P = 0.02) and sTNFR2 (r = 0.51, P < 0.001). Conclusion: Tumor necrosis factor‐α may cause NT‐proBNP elevation in the acute phase of KD, and NT‐proBNP level may be an indicator of TNF‐α activity.